School Engagement and the Role of Peer Victimization, Depressive Symptoms, and Rumination. (August 2019) - Dorio, Nicole B.; Secord Fredrick, Stephanie; Demaray, Michelle K.
The purpose of the current study was to explore the association between peer victimization and school engagement and the indirect effects of rumination and depressive symptoms in this association. Data on middle school students' victimization experiences, school engagement, rumination, and depressive symptoms were collected from 887 sixth- through eighth-grade students utilizing self-report measures. Results indicated for both boys and girls a significant negative association between peer victimization and school engagement. Furthermore, a significant indirect effect of rumination and depression symptoms was evident for both boys and girls, but these effects were more robust for girls. Furthermore, the direct relation between depressive symptoms and school engagement was stronger for girls. Implications of these findings are discussed.